Long Non-coding RNA HOTTIP Promotes CCL3 Expression and Induces Cartilage Degradation by Sponging miR-455-3p - Mao, Guping; Kang, Yan; Lin, Ruifu; Hu, Shu; Zhang, Ziji; Li, Hongyi; Liao, Weiming; Zhang, Zhiqi (Frontiers in Cell and Developmental Biology, 2019)
Long noncoding RNAs (lncRNAs) play pivotal roles in diseases such as osteoarthritis (OA). However, knowledge of the biological roles of lncRNAs is limited in OA. We aimed to explore the biological function and molecular mechanism of HOTTIP in chondrogenesis and cartilage degradation. We used the human mesenchymal stem cell (MSC) model of chondrogenesis, in parallel with, tissue biopsies from normal and OA cartilage to detect HOTTIP, CCL3, and miR-455-3p expression in vitro. Biological interactions between HOTTIP and miR-455-3p were determined by RNA silencing and overexpression in vitro. We evaluated the effect of HOTTIP on chondrogenesis and degeneration, and its regulation of miR-455-3p via competing endogenous RNA (ceRNA). Our in vitro ceRNA findings were further confirmed within animal models in vivo. Mechanisms of ceRNAs were determined by bioinformatic analysis, a luciferase reporter system, RNA pull-down, and RNA immunoprecipitation (RIP) assays. We found reduced miR-455-3p expression and significantly upregulated lncRNA HOTTIP and CCL3 expression in OA cartilage tissues and chondrocytes. The expression of HOTTIP and CCL3 was increased in chondrocytes treated with interleukin-1β (IL-1β) in vitro. Knockdown of HOTTIP promoted cartilage-specific gene expression and suppressed CCL3. Conversely, HOTTIP overexpression reduced cartilage-specific genes and increased CCL3. Notably, HOTTIP negatively regulated miR-455-3p and increased CCL3 levels in human primary chondrocytes. Mechanistic investigations indicated that HOTTIP functioned as ceRNA for miR-455-3p enhanced CCL3 expression. Taken together, the ceRNA regulatory network of HOTTIP/miR-455-3p/CCL3 plays a critical role in OA pathogenesis and suggests HOTTIP is a potential target in OA therapy.